Investigation of chiral porphyrin aggregates with heterodyne-detected vibrational sum frequency generation spectroscopy - Lindberg, Kathryn A., author; Krummel, Amber, advisor; Levinger, Nancy, committee member; Sambur, Justin, committee member; Gelfand, Martin, committee member (Colorado State University. Libraries, 2018)
In nature, photosynthetic organisms harvest and transport solar energy through the finely-tuned interplay between vibrational, electronic, and excitonic characteristics within photosynthetic reaction centers. These characteristics depend intimately on the precise arrangement of the reaction centers' molecular building blocks. Further knowledge of the relationship between structure and function in these natural systems is key to advancing synthetic solar technologies like dye-sensitized solar cells and artificial photosynthesis. Photosynthetic pigments, such as chlorophyll and bacteriochlorophyll, are of particular interest since their absorptive role is the first step in the solar harvesting process. Porphyrins, a group of macrocyclic organic compounds closely related to these pigments, have gained attention as simpler models for their more complicated natural counterparts. Tetra(4-sulfonatophenyl) porphyrin (TSPP), which closely resembles bacteriochlorophyll, is particularly valuable because it forms molecular aggregates analogous to the highly quantum-efficient light-harvesting "antennae" present in green sulfur bacteria chlorosomes. Imaging and spectroscopic studies indicate that the helical nanotubular TSPP aggregates are chiral and have distinct exciton contributions along different axes. However, the precise arrangement of TSPP monomers within the aggregate walls is still debated, prompting further, more detailed studies. Heterodyne-detected vibrational sum frequency generation (HD-VSFG) spectroscopy is a phase-sensitive, second-order nonlinear technique which probes the vibrational characteristics of noncentrosymmetric molecular environments. HD-VSFG experiments can also probe excitonic and vibronic characteristics via experimental double resonance. By use of polarization conditions, theoretical modeling, and computational fitting, detailed information on the orientation of vibrational, vibronic, and excitonic transition dipoles can be extracted from HD-VSFG spectra. This work presents doubly-resonant HD-VSFG spectra of TSPP thin films drop-cast on gold, which demonstrates the technique's sensitivity to the relationship between complex phase and excitonic versus monomeric characteristics. HD-VSFG is then used to compare spectra of TSPP thin films prepared from racemic and chiral aqueous solutions. This comparison includes a polarization condition sensitive to only chiral environments, further demonstrating HD-VSFG as a valuable tool in the structural investigation of TSPP aggregates.
Keywords: HD-VSFG; porphyrin; TSPP; nonlinear spectroscopy; aggregates; sum frequency generation